Personal religion in domestic contexts during the New Kingdom : the impact of the Amarna period - Castro, Iria Souto, (Archaeopress Egyptology ;, 2023)
This study has three main themes: the definition of personal religion and religious domestic practices from a theoretical perspective; the description and analysis of the main archaeological and anthropological evidence; and, on that basis, the study of the impact of the Amarna period in the development of personal religion during the New Kingdom.